A study of highly conductive pattern by manual printing of graphene nanoparticles with different width size - Saad, Hartini (2021)
The development of variety printing methods and compatible conductive inks is to support the emerging high demand production of printed electronic devices. Conductive ink is used to create conductive paths as interconnecting tracks for the printed electronic devices. Extensive research has been performed to produce lightweight conductive ink using composite materials with high electrical conductivity, environmental stability, and good engineering properties. The method of integrating various conductive materials using thermoplastic viscous paste was introduced in order to enhance the ability of conductive ink to conducts electricity. Carbon nanomaterial’s offer many opportunities in the conductive ink application especially for printed and flexible electronics. Therefore, this study aims to produce highly functional conductive ink using graphene nanoparticles with epoxy as a binder by investigate the mechanical and electrical behaviors of newly formulated graphene nanoparticles conductive ink at of different pattens and width. Graphene filler conductive ink was formulated using a minimum percentage of filler loading and increased based on the required conductivity level. The effect of sheet resistivity, nanoindentation, hardness elastic modulus and surface roughness for straight line shape, curve shape, square shape and zigzag shape circuit printed on thermoplastic polyurethane (TPU) substrate were observed in this study at fixed circuit widths of 1 mm, 2.mm and 3 mm. ASTM F390 four point probe and ASTM E2546-1 methods was used to evaluate the electrical, mechanical properties and dynamic ultra-micro hardness of the formulated grapheme filler conductive ink. The lowest value of sheet resistivity was at 1 mm of width at 13972.306 Q/sq and the highest was at 2 mm of width at 280818.944 Q/sq for most of the patterns. Nanoindentation exhibited the improvement of indentation properties with an increasing percentage of filler loading. The penetration depth for newly formulated graphene nanoparticles conductive ink decreases for all patterns except for square patterns as the width increases. Overall obtained results showed that a straight line pattern produced good performance because the performance of a printed line was dictated by its geometry.